EXPLORING THE INTRINSIC LITERARY ELEMENTS OF “LASKAR PELANGI” A NOVEL BY ANDREA HIRATA - Fadhilawati, Dian (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2023)
This qualitative study aims to explore the intrinsic literary aspects of "Laskar Pelangi" by Andrea Hirata, focusing on themes, character development, plot, Settings, language styles, narrative perspective, and moral values. Employing a research approach involving close textual analysis, thematic examination, character studies, linguistic nuances, and narrative perspectives, we dissected the multifaceted nature of the novel. The analysis revealed intricately developed characters, each embodying resilience and hope, while the narrative techniques, including vivid descriptions, dialogues, and cultural nuances, enriched the immersive experience. The thematic exploration highlighted the novel's profound messages about perseverance, the transformative power of education, and the enduring influence of dedicated mentors. Furthermore, the novel's language style use and narrative perspectives were found to enhance reader engagement and emotional connection. As a result, "Laskar Pelangi" emerged as a testament to the moral values of determination, camaraderie, and the pursuit of knowledge, resonating universally. These findings have significant implications for both literary scholarship and educational discourse, emphasizing the enduring relevance of the novel's themes as valuable educational resources. It also underscores the pivotal role of literature in conveying universal insights into the human condition and storytelling's power to inspire individuals facing adversity, while illuminating the impact of language style use and narrative perspective in enhancing the effectiveness of the literature.AbstractPenelitian kualitatif ini bertujuan untuk mengexplorasi  unsur-unsur intrinsik dari "Laskar Pelangi"  sebuah novel karya Andrea Hirata, dengan fokus pada tema, penokohan, alur cerita, gaya bahasa, sudut pandang naratif, dan nilai-nilai moral. Dengan menggunakan pendekatan penelitian yang melibatkan analisis teks yang mendalam, analysis tematik, studi karakter, nuansa linguistik, dan sudut pandang naratif, kami menguraikan sifat yang kompleks dari novelini.  Hasil penelitian mengungkapkan bahwa karakterpada novel  masing-masing menggambarkan ketahanan dan harapan, sementara teknik naratif, termasuk deskripsi yang jelas, dialog, dan nuansa budaya, memperkaya pengalaman yang mendalam. Eksplorasi tematis menyoroti pesan mendalam novel ini tentang ketekunan, kekuatan transformatif pendidikan, dan pengaruh yang berlangsung dari mentor yang berdedikasi. Selain itu, penggunaan gaya bahasa dan sudut pandang naratif dalam novel ini ditemukan meningkatkan keterlibatan pembaca dan koneksi emosional. Sebagai hasilnya, "Laskar Pelangi" muncul sebagai bukti nilai-nilai moral keteguhan, persaudaraan, dan pencarian pengetahuan, meresap secara universal. Temuan ini memiliki implikasi penting baik untuk penelitian sastra maupun wacana pendidikan, menekankan relevansi abadi tema-tema dalam novel ini sebagai sumber pendidikan berharga. Ini juga menggarisbawahi peran penting sastra dalam menyampaikan wawasan universal tentang kondisi manusia dan kekuatan cerita untuk menginspirasi individu yang menghadapi kesulitan, sambil menerangi dampak penggunaan gaya bahasa dan sudut pandang naratif dalam meningkatkan efektivitas karya sastra